Risk factors and outcome of malformations of gastrointestinal tract in neonates in a tertiary care center in India - Shobhna Gupta; Krishan Kumar; Novy Gupte; Deepak Bagga; R. M. Pandey; Harish Chellani (Indian Journal of Child Health, 2021)
Objective: The objective of the study was to determine the prevalence and associated risk factors of malformations of the gastrointestinal tract (MGIT) in neonates in a tertiary care hospital. Methods: We conducted a prospective, observational, case–control study on all intramural neonates till discharge/outcome for 1 year. Babies with MGIT diagnosed antenatally or postnatally were taken as cases and two consecutively born healthy babies were taken as controls. Results: Out of 25,116 live births, there were 41 cases of MGIT with a prevalence of 1.63 per 1000 live births. Tracheoesophageal fistula was the most common (39.02%), followed by anal atresia (24.39 %), esophageal atresia (9.46%), and mesenteric cyst (7.31%). Antenatally and postnatally, 16 (39.1%) and 25 (60.9%) cases were diagnosed, respectively. A significant association was observed between MGIT and lack of periconceptional iron/folic acid supplementation, birth weight 30 years, low socioeconomic profile, consanguinity, febrile illness in first trimester, and gender. The average time to onset of first feed and mean duration of hospital stay in babies with MGIT were 7 days and 14 days, respectively. Conclusion: Most MGIT can be diagnosed clinically and radiologically before/soon after birth and have a good outcome with timely surgical intervention. Pre-pregnancy counseling for periconceptional folic acid supplementation with screening ultrasonography, appropriate follow-up, and referral system should be developed for the management of these cases. A coordinated multidisciplinary approach for prevention, management, and rehabilitation of affected babies is required.